Four new species of Pselaphodes Westwood (Coleoptera: Staphylinidae: Pselaphinae) from Thailand, Laos, and China - Huang, Meng-Chi; Li, Li-Zhen; Yin, Zi-Wei (Zootaxa, 2018)
Four new species of Pselaphodes Westwood are described from southern Asia: P. femoralis sp. n. (China, Thailand), P. incisus sp. n. (China, Laos), P. suthepensis sp. n. (Thailand), and P. thailandicus sp. n. (Thailand), supported by illustrations of male habitus and major diagnostic characters. One of the new species (P. femoralis) exhibits considerable intraspecific variation in the aedeagal structure, but may be readily distinguished by a stable combination of unique male external features.